Modelling of sound reduction of sound insulating enclosure with recycled rubber covered walls - Vilniškis, Tomas; Januševičius, Tomas (International Conference “Environmental Engineering”, 2023)
The excessive noise of machines and devices could be reduced with the use of acoustic enclosures. Additional requirement for enclosures: free air circulation through construction walls, which is important for device ventilation. The acoustic properties of the construction parts are essential to model their ability to reduce noise. The basic properties of airborne sound insulation of construction walls and absorption of used material should be experimentally tested. In this article, sound reduction modelling of acoustic enclosure with recycled materials covered walls was presented. Sound pressure level reduction of enclosure was modelled with Odeon software. A 3D model was created that includes the acoustic properties of the materials used. The enclosure walls consist of two different constructions. The side walls and roof were made from a single plasterboard covered with recycled rubber material. The back and front walls were constructed as louver construction, which plates were mounted with the ability to change the tilt angle which allows to create an air transparent construction. Acoustic properties of the materials used were tested in different ways. Sound absorption properties of 50 mm thick sample of recycled rubber and transmission loss parameters of used sound insulating walls were measured in the impedance tube. The results of the experimental test of the construction parts were included in the 3D model. The modelling results represented a decrease in sound pressure levels with an increasing distance from the enclosure on different sides. Four different enclosures with different tilt angle of louver plates (0°, 15°, 30°, 45°) were modelled. Results were presented in the 125–4000 Hz frequency range. According to the results, efficiency of enclosure sound reduction with 45° tilted plates could reach up to 12 dB.